2016
DOI: 10.1177/1359105316640061
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial distress in women diagnosed with gynecological cancer

Abstract: Many women with gynecological cancer report psychosocial distress, and clarification of the risks, vulnerabilities, and protective factors is required. The aim of this study was to investigate the lived experience of gynecological cancer patients and to understand the factors that underlie psychosocial distress. Semi-structured interviews with seven women diagnosed with gynecological cancer revealed the role of social support, or its absence, selective withholding of information, and existential loneliness in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…We therefore believe that this study has a high likelihood of representing patient populations found in the average gynecologic oncology clinic. The high prevalence of moderate to severe symptomatology in our patient cohort is comparable to other studies assessing HRQL in patients with gynecologic cancer [9][10][11]. Gynecologic oncology patients experience a high burden of symptoms regardless of their stage or cancer type [12].…”
Section: Discussion/significancesupporting
confidence: 81%
“…We therefore believe that this study has a high likelihood of representing patient populations found in the average gynecologic oncology clinic. The high prevalence of moderate to severe symptomatology in our patient cohort is comparable to other studies assessing HRQL in patients with gynecologic cancer [9][10][11]. Gynecologic oncology patients experience a high burden of symptoms regardless of their stage or cancer type [12].…”
Section: Discussion/significancesupporting
confidence: 81%
“…The report recommends that patients undergoing vulvectomy should receive detailed information before and after surgery, and psychosexual counselling should be offered to both patient and her sexual partner on a long-term basis. Psychosocial distress in women diagnosed with cancer is outlined in a study by Warren et al 8 Here researchers investigated the lived experience of patients in order to understand the underlying factors to psychosocial distress, using a qualitative research design to elicit and interpret women’s narratives of gynaecological cancer. The study revealed the role of social support, or its absence and recommends that interventions to address concerns may lead to improved quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research, both quantitative and qualitative, has investigated distress and mental health disorders in gynaecological cancer patients (Reuter, Raugust, Marschner, & Haertner, 2007; Stewart, Wong, Duff, Melancon, & Cheung, 2001), as well as support (Beesley et al, 2008; Ussher, Kirsten, Butow, & Sandoval, 2006; Walton et al, 2010), informational (Booth, Beaver, Kitchener, O’Neill, & Farrell, 2005) and psychosocial needs (Miller, Pittman, & Strong, 2003; Warren, Melrose, Brooker, & Burney, 2016). Additionally, qualitative research has expanded to explore the experience of cancer, particularly in relation to topics such as hope (Hammer et al, 2013; Reb, 2007), meaning (Akyüz, Güvenç, Üstünsöz, & Kaya, 2008; Roberts & Clarke, 2009; Sekse et al, 2010), the impact of childlessness or loss of fertility for younger women (Molassiotis et al, 2002; Roberts & Clarke, 2009) and changing family roles (Akyüz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%